Overexpression of eis without a mutation in promoter region of amikacin- and kanamycin-resistant Mycobacterium tuberculosis clinical strain - Angkanang Sowajassatakul; Therdsak Prammananan; Angkana Chaiprasert; Saranya Phunpruch (My University, 2018)
Aminoglycosides such as amikacin and kanamycin are effective injectable second-line drugs for treatment of multidrug-resistant tuberculosis. Molecular mechanisms underlying aminoglycoside resistance are not well understood. We have previously identified the amikacin- and kanamycin-resistant M. tuberculosis MT433 clinical strain, of which all known mutations related to resistance have not been found. Drug efflux pump is one of reported resistance mechanisms that might play a role in aminoglycoside resistance.The expression levels of sixteen putative efflux pump genes, including eis and one regulator gene, whiB7, of MT433 in the presence of kanamycin were determined using the reverse transcription-quantitative PCR method. The effects of upregulated genes on amikacin and kanamycin resistance were investigated by overexpression in M. tuberculosis H37Ra strain.Upon kanamycin exposure, other than whiB7 and eis that were found extremely overexpressed, two drug efflux pump genes, namely Rv1877 and Rv2846c, showed specifically high-level of expression in M. tuberculosis MT433 strain. However, direct effect of overexpressed Rv1877 and Rv2846c on amikacin and kanamycin resistance could not be demonstrated in M. tuberculosis H37Ra overexpressed strain.Our finding demonstrated that overexpression of eis could occur without any mutations in the promoter region and be detectable in clinical isolate. This might be a consequence of overexpressed whiB7, resulting in amikacin and kanamycin resistance in M. tuberculosis MT433 strain.
Keywords: Kanamycin; Amikacin; Efflux; Capreomycin; Tuberculosis Research and Epidemiology